Determinants of Africa’s development: An exploratory study - Veiga, J.; Ferreira-Lopes, A.; Carvalho, H.; Sequeira, T. N.; Monteiro, H. (Journal of Developing Areas, 2022)
The increasing sustainability and the causes of economic growth in African countries, provide a set of new research questions for development scholars around the World. The possible determinants of this phenomenon are usually considered to be of economic, social, and institutional natures. In this work is assessed which economic, social, and institutional determinants of economic development are important to the development of Africa countries, for the years 1996 and 2014. The similarities amongst countries and the evolution between the two years are also analyzed. A principal components analysis for categorical data to examine the inter-relationships between the indicators in 1996 and also in 2014. An agglomerative clustering algorithm was used through two different methods: ward’s method and complete linkage method (also called furthest neighbor). The Hierarchical Cluster Analysis (HCA) was suited by a k-means algorithm, to obtain an optimal solution and a typology of countries was identified for each year. The main contribution of the work is to make a joint analysis of the three determinants of economic growth and development – economic, social, and institutional, in which the literature is extremely scarce. Results indicate a positive association amongst institutional, economic, and social determinants of development, which means that countries that exhibit a good performance in institutional indicators also have a good performance in economic and social indicators, and vice-versa, although results are not as clear for 2014 as they are for 1996. Additionally, a higher concentration of countries in the two clusters in which these three indicators are better in 2014 (31 countries in 1996 and 49 countries in 2014), seems to indicate a positive evolution for development of African countries from 1996 to 2014. Results show that policy makers should take an integrated view regarding development and economic growth policies and take in consideration both the economic, social, and institutional characteristics of each country. If an economic, social, or institutional policy is designed independently of the other two, this policy will probably fail in reaching its development or economic growth goal, since all these three factors are interconnected.